1985
DOI: 10.1089/jir.1985.5.169
|View full text |Cite
|
Sign up to set email alerts
|

The Interferon Compartment of the Immune Response in Human Malaria: II. Presence of Serum-Interferon Gamma Following the Acute Attack

Abstract: The present study concerns the monitoring of serum-interferon (serum-IFN) levels among 189 patients followed after and sometimes during an acute episode of malaria due mainly to Plasmodium falciparum (P. falciparum). Of these patients, 110 known to have no other parasitic or infectious disease were followed in France; 79 were from Thailand, among which 25 cases of neuromalaria were diagnosed. In a first four-month survey conducted in France, among 100 patients seen after the acute attack, serum-IFN-gamma was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
2

Year Published

1988
1988
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 7 publications
0
18
2
Order By: Relevance
“…Most investigators have found no correlation of serum IFN-'y levels with parasite density, disease severity, or the occurrence of cerebral involvement in patients with malaria (21,24,(34)(35)(36). In the present study, IFN-y levels had normalized in the parasitemic volunteers before parasite density could increase or serious complications could develop, and a triggering role for IFN-y in severe malaria could conceivably be missed in clinical studies due to its transient and early nature.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Most investigators have found no correlation of serum IFN-'y levels with parasite density, disease severity, or the occurrence of cerebral involvement in patients with malaria (21,24,(34)(35)(36). In the present study, IFN-y levels had normalized in the parasitemic volunteers before parasite density could increase or serious complications could develop, and a triggering role for IFN-y in severe malaria could conceivably be missed in clinical studies due to its transient and early nature.…”
Section: Discussioncontrasting
confidence: 65%
“…Ethical considerations dictated prompt treatment of the parasitemic volunteers early in their illness. The studies reported here therefore differ from those done previously in field settings in which cytokirie levels were evaluated in patients primarily after they had become ill ( 14,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Our present observations indicate that the contribution of T cells consists at least in part in producing IFN-'y. Production of IFN-y, which is related to T-cell activation, has been described during murine malaria infection, and elevated levels of IFN-y have been reported in the serum of patients with malaria (13,14). It is evident from in vitro and in vivo studies that both IFN-y and TNF can participate in the killing of malaria parasites inside erythrocytes (15).…”
Section: Discussionmentioning
confidence: 99%
“…65 Genetic association studies have linked IFN-␣ receptor polymorphisms with protection from CM in an African population. 66 In addition, IFN-␣ levels have been detected in PbA 67 and P. falciparum infections, 68 with lower levels of IFN-␣ observed in cases of severe malaria. 41 Little is known about the relationship between type I interferon responses and malarial disease, but type I interferon responses may play a beneficial role for the host in malaria.…”
Section: Org)mentioning
confidence: 99%